Кадровые риски: природа и формы их проявления - Хайнюк, А.С.; Ячменева, В.М. (Культура народов Причерноморья, 2014)
В статье приведена авторская интерпретация понятия "Кадровые риски". Анализ
существующих классификаций кадровых рисков позволил выявить их особенности, (качественные,
количественные, ценностные, организационно-управленческие, личностные). Существующие подходы к
группировке понятий (целостные и информационные) позволили установить причинно-следственные
связи между результатами и целями конкретного исследования. У статті наведена авторська інтерпретація поняття "Кадрові ризики". Аналіз існуючих
класифікацій кадрових ризиків дозволив виявити їх особливості, (якісні, кількісні, ціннісні, організаційно-
управлінські, особистісні). Існуючі підходи до угруповання понять (цілісні і інформаційні) дозволили
встановити причинно-наслідкові зв'язки між результатами і цілями конкретного дослідження. The article presents the author's interpretation of the concept of "Human risks." The study
investigated the behavior of threats depending on the environment and its display subsystem, if the external
environment a threat remains as a threat, as a result of penetration into the internal environment of the
enterprise, the threat manifests itself in the form of risk, each of these manifestations has positive and negative
consequences. Revealed that in order to achieve the expected result as the internal and external environment is
necessary to use administrative measures to reduce the impact in the form of damages or to benefit. A
prerequisite for the management of human risk is their study, which reveals the risks and their components, as
well as actions related to personnel that may pose a risk to the enterprise. For effective impact on human risk of
needing their classification, which allows you to effectively apply the techniques, methods and techniques of risk
management. Analysis of existing classifications of personnel risks revealed their characteristics (qualitative,
quantitative, values, organizational, managerial, personal), that allows to predict the emergence and
manifestation of human risks. Existing approaches to grouping of concepts (integrity and information) allowed
to establish causal relationships between the results and the objectives of a particular study.